Nitric Oxide Is Associated With Heterosis of Salinity Tolerance in Brassica napus L. - Zhang, Yihua; Cheng, Pengfei; Wang, Jun; Abdalmegeed, Dyaaaldin; Li, Ying; Wu, Mangteng; Dai, Chen; Wan, Shubei; Guan, Rongzhan; Pu, Huiming; Shen, Wenbiao (Frontiers in Plant Science, 2021)
Heterosis is most frequently manifested as the superior performance of a hybrid than either of the parents, especially under stress conditions. Nitric oxide (NO) is a well-known gaseous signaling molecule that acts as a functional component during plant growth, development, and defense responses. In this study, the Brassica napus L. hybrid (F1, NJ4375 × MB1942) showed significant heterosis under salt stress, during both germination and post-germination periods. These phenotypes in the hybrid were in parallel with the better performance in redox homeostasis, including alleviation of reactive oxygen species accumulation and lipid peroxidation, and ion homeostasis, evaluated as a lower Na/K ratio in the leaves than parental lines. Meanwhile, stimulation of endogenous NO was more pronounced in hybrid plants, compared with parental lines, which might be mediated by nitrate reductase. Proteomic and biochemical analyses further revealed that protein abundance related to several metabolic processes, including chlorophyll biosynthesis, proline metabolism, and tricarboxylic acid cycle metabolism pathway, was greatly suppressed by salt stress in the two parental lines than in the hybrid. The above responses in hybrid plants were intensified by a NO-releasing compound, but abolished by a NO scavenger, both of which were matched with the changes in chlorophyll and proline contents. It was deduced that the above metabolic processes might play important roles in heterosis upon salt stress. Taken together, we proposed that heterosis derived from F1 hybridization in salt stress tolerance might be mediated by NO-dependent activation of defense responses and metabolic processes.